Effect of Co concentration on the Y0.1Ca0.9Zr1-xCoxO3-δ limiting current dense diffusion barrier oxygen sensor. Issue 4 (15th February 2023) - Tan, Wendong; Li, Jinlian; Zhang, Xiaofang; You, Jiegang; Wang, Yakai; Xi, Zhuoyi; Wang, Xiangnan; Luo, Xudong
Abstract: Y0.1 Ca0.9 Zr1- x Co x O3-δ ( x  = 0, 0.1, 0.3, and 0.5) was synthesized by a solid-state reaction. Y0.1 Ca0.9 Zr1- x Co x O3-δ is orthorhombic perovskite structure. The electronic conductivity and total conductivity increase with increasing Co concentration and temperature. The activation energy of electronic conductivity and total conductivity is lowest when the Co concentration is x  = 0.5. A lower activation energy is conducive to the migration of oxygen ions. Using Y0.1 Ca0.9 Zr0.7 Co0.3 O3-δ and Y0.1 Ca0.9 Zr0.5 Co0.5 O3-δ as dense diffusion barrier and 8YSZ (8 mol% yttria-stabilized zirconia) as a solid electrolyte, the limiting current oxygen sensor was fabricated by the Pt sintered-paste method, and its sensing performance was studied. The oxygen sensor exhibits a limiting current plateau at 760–850 °C. The oxygen measurement range increases with increasing Co concentration. The limiting current is directly proportional to the oxygen concentration, indicating that it shows excellent sensing characteristics at different temperatures. When the test time is more than 75 h, the oxygen sensor has good stability, and the stable limiting current is approximately 4.23 mA. The voltage range of the limiting current plateau has no effect on the increase of the detection time, and its voltage range is 0.75–1.75 V.